PENYULUHAN OPTIMALISASI PENGGUNAAN DANA DESA UNTUK PENCAPAIAN SDGS DESA BIDANG KESEHATAN DI DESA KARYAWANGI KECAMATAN PANDEGLANG BANTEN - Rahmawati - Rahmawati (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
The problems of the Karyawangi Village service partners include the low understanding of village officials and the community about the Village SDGs and the priority use of village funds in the health sector is not optimal. This activity aims to provide and improve the understanding of the Karyawangi Village community in Pandeglang Banten about the priority use of village funds and the application of village SDGs in the health sector. Village funds for health development can be in the form of providing additional food for toddlers and pregnant women, handling stunting, providing blood capsules for pregnant women and training for posyandu cadres. The method of counseling was through lectures and discussion of interaction between resource persons and counseling participants. The activity stages are initial observation and preparation of activity plans, implementation of activities and evaluation of activity results. The results of the activity are expected that the use of village funds to achieve village SDGs starts from careful and precise planning, implementation of health programs that are right on target and continuous monitoring and evaluation activities. With an increased understanding of this, it is hoped that the use of village funds to optimize the achievement of SDGs can run effectively and efficiently in Karyawangi Village, Pandeglang. Keywords : health; rural; SDGs; Stunting; Village Fund